Plasma galectin-3 can be considered as a non-invasive marker to predict the prognosis of ACLF patients with new typing - Li Bai; Wang Lu; Qi Yang; Xiaoxuan Liu; Yu Chen; Zhongping Duan (Scientific Reports)
Abstract Very recently, we creatively put forward a new classification for ACLF patients, which lays the foundation for the establishment of prognostic model that can accurately predict the prognosis of ACLF patients. Herein, we found: galectin-3 levels were higher in type A ACLF patients compared to those of type B patients; galectin-3 expression was closely correlated with TBil, PTA/INR and MELD; galectin-3 is an independent predictive factor for rapid progression in ACLF, and exhibited superior predictive value for the prognosis of type A ACLF patients than MELD score; and the survival rate was remarkably higher in ACLF patients with lower galectin-3 expression. Collectively, galectin-3 can be considered as a non-invasive biomarker to predict the prognosis of ACLF patients with new typing. Our findings help advance the time window of prognosis prediction for type A and type B ACLF patients from 4 weeks to the baseline, thereby identifying ACLF patients who really need liver transplantation earlier and improving the survival of ACLF patients.